Exploring the allelopathic autotoxicity mechanism of ginsenosides accumulation under ginseng decomposition based on integrated analysis of transcriptomics and metabolomics - Wang, Rui; Zhou, Tingting; Wang, Yikai; Dong, Jinxu; Bai, Yutao; Huang, Xin; Chen, Changbao (Frontiers in Bioengineering and Biotechnology, 2024)
Continuous cropping obstacles seriously constrained the sustainable development of ginseng industry. The allelopathic autotoxicity of ginsenosides is the key “trigger” of continuous cropping obstacles in ginseng. During harvest, the ginseng plants could be broken and remained in the soil. The decomposition of ginseng residue in soil is one of the important release ways of ginsenosides. Therefore, the allelopathic mechanism of ginsenosides through the decomposed release pathway needs the in-depth study. To investigate this allelopathic regulation mechanism, the integrated analysis of transcriptomics and metabolomics were applied. The prototype ginsenosides in ginseng were detected converse to rare ginsenosides during decomposition. And the rare ginsenosides caused more serious damage to ginseng hairy root cells and inhibited the growth of ginseng hairy roots more significantly. By high-throughput RNA sequencing gene transcriptomics study, the significantly differential expressed genes (DEGs) were obtained under prototype and rare ginsenoside interventions. These DEGs were mainly enriched in biosynthesis of secondary metabolites and metabolic pathways, phytohormone signal transduction, and protein processing in endoplasmic reticulum pathways. Based on the functional enrichment of DEGs, the targeted metabolomics analysis based on UPLC-MS/MS determination was applied to screen endogenous differential metabolized phytohormones (DMPs). The influence of prototype and rare ginsenosides on the accumulation of endogenous phytohormones were studied. These were mainly involved in biosynthesis of diterpenoid, zeatin and secondary metabolites, phytohormone signal transduction and metabolic pathways. Integrated the transcriptomics and metabolomics analysis, ginsenosides could regulate the genes in phytohormone signaling pathways to influence the accumulation of JA, ABA, and SA. The conclusion is that the prototype ginsenosides were converted into rare ginsenosides by ginseng decomposition and released into the soil, which aggravated its allelopathic autotoxicity. The allelopathic mechanism was to intervene the response regulation of genes related to the metabolic accumulation of endogenous phytohormones in ginseng. This result provides a reference for the in-depth study of continuous cropping obstacles of ginseng.